PENGARUH HARGA JUAL DAN SALURAN DISTRIBUSI TERHADAP VOLUME PENJUALAN PRODUK KOPI KAPAL API PADA CV. BINTANG TERANG LAHAT - MARKUS MARKUS (Jurnal Manajemen Bisnis Unbara, 2020)
This study aims to determine (1) influence of selling price and distribution channel to sales volume of product coffee kapal api (2) the effect of selling price on sales volume (3) influence of distribution channel to sales volume. Research subject is CV. BINTANG TERANG LAHAT and sample data is selling price, distribution channel and sales volume year 2012-2016. The data obtained are then analyzed using regression analysis using SPSS application. Based on the analysis obtained Y = 14505.685 + .039 X1 + 35.025 X2+ e which mean constanta value of 14505.685 mean if the independent variables are ignored the value of variable (Y) of 14505.685. the result of the research shows that there is significant effect of selling price (X1), distribution channel (X2), together to the sales volume (Y). The test T influence variable (X1) on (Y) cost (X1) is 8.535 with significant is .013 ≤ 0,05, influence variable (X2) on (Y) cost (X2) is 4.502 with significant level of .046 < 0,05. The test result F obtained 60.058 by taking a significant level of 5% then with a significant level of 0.016 < 0,05.